2019
DOI: 10.1111/bcpt.13243
|View full text |Cite
|
Sign up to set email alerts
|

Gestational exposure to low‐dose zearalenone disrupting offspring spermatogenesis might be through epigenetic modifications

Abstract: Zearalenone (ZEA), a F‐2 mycotoxin produced by Fusarium, has been found to be an endocrine disruptor through oestrogen receptor signalling pathway to impair spermatogenesis. The disruption on reproductive systems by ZEA exposure might be transgenerational. In our previous report, we have found that low dose (lower than no‐observed effect level, NOEL) of ZEA impaired mouse spermatogenesis and decreased mouse semen quality. The purpose of the current investigation was to explore the impacts of low‐dose ZEA on sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
(128 reference statements)
0
14
0
Order By: Relevance
“…Moreover, we found that 5hmC was mainly expressed in spermatogonia stem cells (SSCs; Men et al, 2019). The number of 5hmC-positive SSCs in F0 mouse testes was significantly diminished by NH 4 Cl-50mg/kg, NH 4 Cl-10mg/kg + Na 2 S-10mg/kg, and NH 4 Cl-50 mg/kg + Na 2 S-50 mg/kg exposure ( Figures 3A, B ).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, we found that 5hmC was mainly expressed in spermatogonia stem cells (SSCs; Men et al, 2019). The number of 5hmC-positive SSCs in F0 mouse testes was significantly diminished by NH 4 Cl-50mg/kg, NH 4 Cl-10mg/kg + Na 2 S-10mg/kg, and NH 4 Cl-50 mg/kg + Na 2 S-50 mg/kg exposure ( Figures 3A, B ).…”
Section: Resultsmentioning
confidence: 97%
“…was increased along with the decreased expression of testicular ERα in mice exposed to ZEA (Gao et al, 2015;Men et al, 2019). These studies revealed the crucial role of interactions between the oestrogen signalling pathway and genetic and epigenetic pathways in mediating the adverse effects of ZEA on spermatogenesis (Gao et al, 2015;Men et al, 2019).…”
Section: Epi G Ene Ti C Effec Ts Of Environmental Contaminants On Mmentioning
confidence: 72%
“…was increased along with the decreased expression of testicular ERα in mice exposed to ZEA (Gao et al, 2015;Men et al, 2019). These studies revealed the crucial role of interactions between the oestrogen signalling pathway and genetic and epigenetic pathways in mediating the adverse effects of ZEA on spermatogenesis (Gao et al, 2015;Men et al, 2019). Kim et al reported nonylphenol in-duced pathophysiological abnormalities in testis and epididymis of F2 mice, which were suggested to be a result of epigenetic reprogramming by nonylphenol exposure (Kim et al, 2019).…”
Section: Epi G Ene Ti C Effec Ts Of Environmental Contaminants On Mmentioning
confidence: 92%
“…Concomitantly with these findings, the authors report the disruption of meiosis and decreased sperm quality [ 192 ]. Moreover, the same group—using the same doses—further explored the consequences of prenatal exposure to zearalenone in ICR mice and found that, irrespective of the strain used, a global reduction in both DNA methylation and estrogen alpha can still be observed, paralleled by elevated histone methylation of H3K9 and H3K27 [ 193 ]. Given the effects reported, further attention should be given to zearalenone and caution must be taken when dealing with products contaminated with this EDC.…”
Section: Epigenetic Mechanisms Are Sensitive To Environment and LImentioning
confidence: 99%